AKRAB KOMODIFIKASI KONTEN TELEVISI LINTAS PLATFORM, ANALISA FRAMING PEMBERITAAN KECELAKAAN PESAWAT SRIWIJAYA AIR DI YOUTUBE - RISA KARMIDA (Jurnal Ilmu Komunikasi AKRAB, 2021)
AbstactThe mass media have treated the Sriwijaya Air plane crash on January 9, 2021 as a content commodity that can be re-broadcast across platforms. The three videos raised by the author are Breaking News Metro TV about the crash of the Sriwijaya Air plane, the CNN video titled 'Deep Grief for the Family of the Sriwijaya Air SJ182 Victim', and the Kompas TV video entitled 'The Grief of the Family of the Sriwijaya Air Victim SJ-182. The three news editors dramatized the disaster broadcast by displayed the tears of the victim's family, added sad background music, gave special effects, and interviewed the victim's family to create sad expressions. The dramatization is a commodification that includes the transformation from the use value of disaster broadcasts which should prioritize mitigation, to the economic value of viewer pans. This is not in accordance with the principles of humanity and empathy journalism which should involve journalists' conscience, thus making grief as a spectacle. The Indonesian Broadcasting Commission (KPI) and the Press Council (Dewan Pers) must be stricter in regulating media behavior in disaster coverage. This study uses a qualitative approach with the point of view of the political economy of the mass media. This research analysis method uses framing analysis, to find out how social reality are interpreted and constructed with a certain framework.Keyword: Sriwijaya Air, commodification, disaster dramatization